2015
DOI: 10.1039/c5cc01772f
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of a lithium boryl as a reducing agent in low oxidation state group 15 chemistry: synthesis and characterisation of an amido-distibene and a boryl-dibismuthene

Abstract: The first examples of an amido-distibene, L(†)Sb[double bond, length as m-dash]SbL(†) (L(†) = -N(Ar(†))(SiPr(i)3), Ar(†) = C6H2{C(H)Ph2}2Pr(i)-2,6,4), and a boryl dibismuthene, {(DAB)B}Bi[double bond, length as m-dash]Bi{B(DAB)} (DAB = {(C6H3Pr(i)2-2,6)NCH}2, have been prepared by reaction of a lithium boryl complex, (THF)2LiB(DAB), with extremely bulky amido-group 15 dihalide precursor compounds. In these reactions, the lithium boryl acts as a boryl transfer reagent and/or a strong reducing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 23 publications
5
51
0
2
Order By: Relevance
“…reported on the boryl dibismuthene [(DAB)B]BiBi[B(DAB)] [DAB=(2,6‐ i Pr 2 C 6 H 3 )NCH) 2 ] (Figure 1 D). 18…”
Section: Introductionmentioning
confidence: 99%
“…reported on the boryl dibismuthene [(DAB)B]BiBi[B(DAB)] [DAB=(2,6‐ i Pr 2 C 6 H 3 )NCH) 2 ] (Figure 1 D). 18…”
Section: Introductionmentioning
confidence: 99%
“…Although this latter feature also ensures that the electropositive boron centre retains a significant partial positive charge (for 1 ; calculated natural population analysis charge on B=+0.072), these species behave as boron-centred nucleophiles by dint of a net polarization of the boron–lithium bond (in effect, B δ+ –Li δ++ ) induced by the even lower effective nuclear charge of lithium (for 1 ; calculated natural population analysis charge on Li=+0.755)913. Although a rich and varied chemistry has since arisen from the reactivity of compound 1 and related N- heterocyclic boryl anions with organic914, transition metal15161718 and main group electrophiles1419202122232425, alternative nucleophilic boron reagents remain very rare species262728293031. Notable exceptions are Braunschweig's dimetalloborylene and borolyl anions (for example, 2 and 3 )3233 Bertrand and Kinjo's carbene-stabilised monovalent boron species (for example, 4 )3435363738 and a remarkable tricyanoborandiyl dianion394041.…”
mentioning
confidence: 99%
“…As can been seen from Fig. 24 The planes of the 1,2,4-diazaphospholide in the face-to-face orientation were almost perpendicular to each other, with an average dihedral angle of close to 90°despite the average N-Sb-N angle being 85.0(3)°in 4, 85.6(4) in 5α and 5β, and 85.1(6) in 6. This indicated that the overall ligand arrangement around the Sb 2 core was an almost perfect paddlewheel structure for 5α, 5β, and 6 but a twisted structure (because of steric substituent repulsion) for 4.…”
mentioning
confidence: 69%
“…[22][23][24] The ability to successfully prepare 4-6 was obviously caused by the unique electronic nature of the ligands, suggesting that more extensive p-block paddlewheel 1,2,4-diazaphospholide complexes are possible. The Sb-Sb bond in 4 is very short, even close to the SbvSb double bond distances in distibenes.…”
mentioning
confidence: 99%